2019
DOI: 10.1186/s13256-019-2243-0
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing peritonitis presenting as complete mechanical bowel obstruction: a case report

Abstract: Introduction Sclerosing peritonitis or abdominal cocoon syndrome is characterized by small bowel loops completely encapsulated by a fibrocollagenous membrane in the center of the abdomen. Although cocooning of the abdomen is mostly seen in patients on peritoneal dialysis, it can occur de novo; it very rarely manifests as complete mechanical bowel obstruction. Case presentation A 46-year-old Asian man presented with complete mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…As a result, 97 articles were included in our study. [3–41] The flow diagram of the study is shown in Figure 4. These articles were carefully studied, and a database with the patients’ characteristics was made, which could be available if requested.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, 97 articles were included in our study. [3–41] The flow diagram of the study is shown in Figure 4. These articles were carefully studied, and a database with the patients’ characteristics was made, which could be available if requested.…”
Section: Methodsmentioning
confidence: 99%
“…In most cases the cause of sclerosing peritonitis is unknown. However, patients on long-standing peritoneal dialysis, with peritoneal shunts, and those suffering from abdominal tuberculosis are more prone to develop this fibrous layer around the bowel [ 6 ]. The prevalence of abdominal cocoon syndrome (ACS) is unknown, but among peritoneal dialysis patients, the prevalence is 1.4–7.3% [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cells are always present, but leukocyte infiltration is not a must for diagnosis [14]. In the pathogenesis of cocoon formation, It is thought that fibrogenic cytokines are released from fibroblasts trigger neoangiogenesis and peritoneal fibrosis [15,16].…”
Section: Discussionmentioning
confidence: 99%